Generalization of the CQC3 criterion to include three seismic components in any direction - López, Oscar; Hernández, Julio (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The structural response to three seismic translational components that can form any angle with the directions of structural axes is investigated in this paper. The systems are elastic and the seismic motion is described in terms of a response spectrum for each component, which have identical shapes but different intensities. The GCQC3 method for combining responses to multicomponent seismic motion is proposed, which is a generalization of the well-known CQC3 method that restricts a principal seismic component along the vertical direction. The proposed method allows studying the variability of the response with the direction of the three principal seismic components.